Perancangan Sistem Kontrol Lampu Berbasis Mikrokontroler Arduino Uno R3 dengan Sensor Suara (Studi Kasus : PT. Kopi Oey Cabang Telkom) - Ronni Sahat Hutabarat; Nur Nawaningtyas (Journal of Innovative and Creativity, 2025)
The study purpose was to design and evaluate an automatic light control system based on the Arduino Uno R3 microcontroller integrated with a sound sensor, implemented at PT. Kopi Oey, Telkom Branch. The development of this system was motivated by the growing need for automation in the food and beverage (F&B) industry, aiming to improve energy efficiency, reduce operational errors, and support sustainable business operations through technology- based innovation. Materials and methods. The system was designed to respond to sound input—such as hand claps—detected by a sound sensor connected to the Arduino Uno R3. The microcontroller processes the input and triggers a relay module to turn lights on or off automatically. The system was tested in a real working environment to evaluate functionality and responsiveness. Usability was assessed through a standardized questionnaire measuring five aspects: Learnability, Efficiency, Memorability, Errors, and Satisfaction. Results. All usability aspects scored above 4.4 on a 5-point scale, with Efficiency (4.56) and Memorability (4.55) being the highest, indicating excellent usability and performance. Conclusions. The voice-activated lighting system proved effective, user-friendly, and energy-efficient, offering a practical automation solution for commercial environments and paving the way for future Internet of Things (IoT) integration.